Wifi Network Design for High Performance - Heru Nurwarsito; Kasyful Amron; Bekti Widyaningsih (Bandar Lampung University (UBL), 2013)
Indoor wireless network connectivity is strongly influenced by the presence of interference. Usually transmitted signal can be received in free space or by more than one pathway, because the effects of multipath propagation such as reflection, refraction and scattering of radio waves by the structure of the building, and these effects may be a phenomenon called multipath fading. Multipath Fading is triggered by the presence of loads and very high performance. Propagation model based on user capacity has been identified for possible outcomes, which provide the propagation characteristics as the initial evaluation. Two wireless propagation models, namely empirical and theoretical models related to the coverage, capacity and performance of wireless network users. Empirical and theoretical models used for laying planning system. In addition, this comparison can help to identify the accuracy of the survey measurements when wireless indoor monitoring and it can help to provide an estimate of the coverage and performance of wireless networks in the form of a new topology, along with contour display. Optimization of the planning system laying Wi-Fi user capacity planned by generating an average RSSI reaches -40 dbm to -55 dbm with power 17-18 dbm and canals that channel 1 is applied to 11 non-overlapping in the network design consisting of AP in the adjacent lot. The optimization results are reflected in the new topology along with contour display and spread throughout the area.